Expression of Translationally Controlled Tumor Protein in Human Kidney and in Renal Cell Carcinoma. (3rd September 2015) - Ambrosio, Maria R.; Rocca, Bruno J.; Barone, Aurora; Onorati, Monica; Mundo, Lucia; Crivelli, Filippo; Di Nuovo, Franca; De Falco, Giulia; del Vecchio, Maria T.; Tripodi, Sergio A.; Tosi, Piero
Abstract : Translationally controlled tumor protein is a multifaceted protein involved in several physiological and biological functions. Its expression in normal kidney and in renal carcinomas, once corroborated by functional data, may add elements to elucidate renal physiology and carcinogenesis. In this study, translationally controlled tumor protein expression was evaluated by quantitative real time polymerase chain reaction and western blotting, and its localization was examined by immunohistochemistry on 84 nephrectomies for cancer. In normal kidney protein expression was found in the cytoplasm of proximal and distal tubular cells, in cells of the thick segment of the loop of Henle, and in urothelial cells of the pelvis. It was also detectable in cells of renal carcinoma with different pattern of localization (membranous and cytoplasmic) depending on tumor histotype. Our data may suggest an involvement of translationally controlled tumor protein in normal physiology and carcinogenesis. However, functional in vitro and in vivo studies are needed to verify this hypothesis.